State Regulation of the Agro-Industrial Complex as the Most Important Component for Sustainable Development - AIMURZINA, Baglan; GULZHAN, Alina; DAULETOVA, Aziza; KAMENOVA, Mazken; OMAROVA, Ainura; BEISENGALIYEV, Berik (Journal of Environmental Management and Tourism; Vol 8 No 5 (2017): JEMT Volume VIII Issue 5(21) Fall 2017DO - 10.14505//jemt.v8.5(21).12, 2018)
This article deals with the problems of state financial regulation of the agro-industrial complex of the Republic of Kazakhstan in recent years. It is noted that the strategic importance and specific features of agriculture require the development of special approaches to the management of this industry, its investment at the regional level. The main task of state regulation of the economic development of the industry is the investment development of agricultural production. As investment growth is one of the main factors contributing to the rise of agro-industrial production, solving the problems of updating the regional technical and technological base, deterioration of fixed assets in agriculture, ensuring sustainable development of the agricultural sector of the economy. The analysis of the main sources of the primary incomes of the enterprises of agriculture, forestry and fisheries in Kazakhstan for 2010-2015 is carried out. Proposals on further improvement of the state financial regulation of the republic's agro-industrial complex are given.